Analisis Biaya dan Faktor-Faktor Penentu Inefisiensi Layanan Hemodialisis pada Pasien Gagal Ginjal Kronik Rumah Sakit Rk Charitas Palembang Tahun 2016 - Rusli, Noer Triyanto (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Enactment of JKN in hospital changes the payment system from retrospective payment (fee for service) into prospective payment (INA-CBG's). As a healthcare facility, RK Charitas Hospital has a role to provide not only quality but also to consider cost effective of services. This study aimed to analyze costs and identify the determinants of the inefficiency of hemodialysis services in patients with chronic renal failure at RK Charitas Hospital. This is a descriptive analysis research using primary and secondary data. Approach of cost analysis is Activity Based Costing (ABC) with "Bottom Up" method. ABC method is used to allocate costs by identifying cost drivers of hemodialysis services. Operational cost is the biggest expense in the hemodialysis services. Analysis of the inefficiency factors uses the calculation of Value Stream Mapping (VSM). The composition of value added (VA) compared to non-value added (NVA) is 17.73%: 82.27%. Lean implementation on hemodialysis services could eliminate waste.